2023
DOI: 10.21203/rs.3.rs-2275675/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital Cognitive Tests for Dementia Screening:  A Systematic Review

Abstract: Background: The number of people with dementia is increasing dramatically. With the outbreak of the COVID-19 pandemic, use of digital screening tests can play a significant role in the remote and timely detection of people with dementia. The aim of this study is to review digital cognitive tests for dementia screening. Methods: We searched Web of Science, ProQuest, PubMed, Scopus and Cochrane in June, 2022. 1348 articles were identified. After reviewing the articles and excluding duplicates and irrelevant art… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Generally, in order to monitor disease progression in different domains each patient is examined with several tests and on a regular basis, so their times add up and become large in the long run. An approach to diminish the administration, scoring, interpretation, and documentation times of neuropsychological tests is the usage of computerized or digital cognitive tests [86]. In that recent systematic review those authors found out that almost 60% were mobile-based screening tests; near 3 out of 10, desktop-based; and the rest, web-based.…”
Section: Non-neuroimaging Biomarkers and Diagnosis Criteria In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in order to monitor disease progression in different domains each patient is examined with several tests and on a regular basis, so their times add up and become large in the long run. An approach to diminish the administration, scoring, interpretation, and documentation times of neuropsychological tests is the usage of computerized or digital cognitive tests [86]. In that recent systematic review those authors found out that almost 60% were mobile-based screening tests; near 3 out of 10, desktop-based; and the rest, web-based.…”
Section: Non-neuroimaging Biomarkers and Diagnosis Criteria In Admentioning
confidence: 99%
“…Additionally, these digital versions ease remote and self-administration. However, due to the different way the neuropsychological test is conducted, results for the paper and digital versions of the same test may differ [86].…”
Section: Non-neuroimaging Biomarkers and Diagnosis Criteria In Admentioning
confidence: 99%
“…Besides these classical evaluations, numerous authors have developed new screening tools on numerical tablets that show good correlations with usual tests. Although several recent systematic reviews have been published [7][8][9], only one meta-analysis with good results focused on digital drawing tasks [10]. In all these studies, numerical tests could run either on numerical tablets or simple computer touch screens and were self or hetero-administered.…”
Section: Introductionmentioning
confidence: 99%